Two new species of genus Karschia Walter, 1889 (Solifugae, Karschiidae) from northwest China - Fan, Wenlong; Zhang, Chao; Zhang, Feng (Zootaxa, 2024)
Two new species of the solifugae genus Karschia Walter, 1889, are described from northwest China. A detailed morphological description, diagnostic features, and illustrations of Karschia (Karschia) latuis sp. nov. and Karschia (Karschia) wenquan sp. nov. are provided. The current distribution of all the known Karschia Walter, 1889 species from China is mapped.